A SYSTEMATIC APPROACH TO SOURCE-SINK MATCHING FOR CO2 EOR AND SEQUESTRATION - Usman Pasarai; Utomo Pratama Iskandar; Sugihardjo Sugihardjo; Herru Lastiadi S (Scientific Contributions Oil and Gas, 2013)
Carbon dioxide for enhanced oil recovery (CO2 EOR) can magnify oil production substantially while aconsistent amount of the CO2 injected remains sequestrated in the reservoir, which is benefi cial for reducingthe greenhouse gas (GHG) emission. The success of CO2 EOR sequestration depends on the proper sourcessinksintegration. This paper presents a systematic approach to pairing the CO2 captured from industrialactivities with oil reservoirs in South Sumatra basin for pilot project. Inventories of CO2 sources and oilreservoirs were done through survey and data questionnaires. The process of sources-sinks matching waspreceded by scoring and ranking of sources and sinks using criteria specifi cally developed for CO2 EORand sequestration. The top candidate of CO2 sources are matched to several best sinks that correspond toadded value, timing, injectivity, containment, and proximity. Two possible scenarios emerge for the initialpilot where the CO2 will be supplied from the gas gathering station (GGS) while the H3 and F21 oil fi eldsas the sinks. The pilot is intended to facilitate further commercial deployment of CO2 EOR sequestrationin the South Sumatera basin that was confi rmed has abundant EOR and storage sinks as well as industrialCO2 sources.